Interlink between pharyngeal radiation dose and long-term quality of life in HNSCC patients - Sivakamavalli Jeyachandran (Oral Oncology Reports)
Head and neck squamous cell carcinoma (HNSCC) encompass cancers originating in the head and neck mucosal surfaces, including the oral cavity, pharynx, and larynx. Standard treatments involve surgery, radiation therapy, chemotherapy, or combinations thereof. Radiation therapy, targeting pharyngeal cancer cells, is common but can damage critical structures, affecting quality of life (QoL). Dysphagia, xerostomia, speech difficulties, and pain are prevalent side effects. Research shows radiation dose correlates with severity of these effects; sparing healthy tissue reduces side effects. Advanced techniques like intensity-modulated radiation therapy (IMRT) and proton therapy offer precise tumor targeting, sparing normal tissues. Ongoing research aims to refine techniques for better long-term outcomes in HNSCC patients.